2014
DOI: 10.1089/sur.2012.156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vacuum-Assisted Closure in Bacterial Clearance of the Infected Abdomen

Abstract: Superinfection is common in laparostomy done with a VAC device for managing severe abdominal infection. The data in the present study show that VAC does not alter the quality of the bacterial burden in primary abdominal contamination, nor does it seem to prevent a high incidence of HAPI. However, VAC is as effective in reducing mortality among patients with HAPI as among those without it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…Although covered with occlusive negative pressure dressings, the laparostomy wound creates a potential route for pathogens to enter the abdominal cavity. In a recent study Pliakos et al [ 27 ] showed in 39 patients with severe abdominal sepsis treated with open abdomen and VAC that 54 % of the patients developed a hospital-acquired peritoneal infection during the VAC-treatment. We observed a similar trend with 34 % of patients being colonized at the primary laparostomy and 89 % after two weeks of OA treatment, although a significant number of our patients had initially a non-contaminated surgical field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although covered with occlusive negative pressure dressings, the laparostomy wound creates a potential route for pathogens to enter the abdominal cavity. In a recent study Pliakos et al [ 27 ] showed in 39 patients with severe abdominal sepsis treated with open abdomen and VAC that 54 % of the patients developed a hospital-acquired peritoneal infection during the VAC-treatment. We observed a similar trend with 34 % of patients being colonized at the primary laparostomy and 89 % after two weeks of OA treatment, although a significant number of our patients had initially a non-contaminated surgical field.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa, Enterobacter species and Candida species [ 29 , 30 ], all of which were detected as colonizing pathogens also in the present study. Pliakos et al showed predominance of intestinal bacteria in the OAs of patients treated for peritonitis [ 27 ] many of these also belonging to the previously mentioned families of resistant microbes. In particular, postoperative isolation of Enterococci, observed as the most commonly cultured pathogens from the OAs in the present study, has been associated with treatment failure and death [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we should focus not only on the treatment of primary disease in elderly patients but also take effective measure to treat SAP to significantly improve the life quality and prognosis of patients in Neurosurgery Department. Furthermore, multi-drug resistance bacteria infection [20][21][22] can prolong the hospitalization time of SAP patients increase the hospitalization cost and even increase the mortality [23,24]. Gram-negative bacteria are most common in SAP patients with multi-drug resistance bacteria infection.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the minimum required treatment, such as lavage and drainage, is carried out with the abdomen open, followed by general management in the intensive care unit for patients with severe peritonitis. 7,8 Although OAM was originally proposed as a damage-control strategy in patients with severe trauma, the technique has been adapted for non-trauma patients, including those with severe peritonitis. 2,3 In this case, it took 32 days for fascial closure from first laparotomy.…”
Section: N Open Abdominal Drainage For Peritonitis Primarymentioning
confidence: 99%